2022
DOI: 10.1021/jacs.2c01679
|View full text |Cite
|
Sign up to set email alerts
|

Role of a “Magic” Methyl: 2′-Deoxy-2′-α-F-2′-β-C-methyl Pyrimidine Nucleotides Modulate RNA Interference Activity through Synergy with 5′-Phosphate Mimics and Mitigation of Off-Target Effects

Abstract: Although 2′-deoxy-2′-α-F-2′-β-C-methyl (2′-F/Me) uridine nucleoside derivatives are a successful class of antiviral drugs, this modification had not been studied in oligonucleotides. Herein, we demonstrate the facile synthesis of 2′-F/Me-modified pyrimidine phosphoramidites and their subsequent incorporation into oligonucleotides. Despite the C3′-endo preorganization of the parent nucleoside, a single incorporation into RNA or DNA resulted in significant thermal destabilization of a duplex due to unfavorable e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…Later studies by several groups showed that a single UNA modification at position 7 of the seed region (nucleotides 2–8 of the guide strand) strongly reduced miRNA-like off-target activity while maintaining the desired on-target activity of siRNAs. , The authors proposed that UNA modification reduced the off-target activity by thermodynamic destabilization of the seed–mRNA complex, which at position 7 was more critical for the partially complementary miRNA off-targets than for the fully complementary siRNA targets. , Consistent with this notion, other thermally destabilizing modifications, such as 2′-F/Me at position 7 (Figure ) or substitution of all eight seed ribonucleotides with DNA reduced the miRNA-like off-target activity of the modified guide strands. Beal and co-workers showed that the 1-ER triazole nucleobase substitution (Figure ) at the first position of the guide strand (G1) improved siRNA specificity by reducing the miRNA-like off-target activity while improving the on-target activity .…”
mentioning
confidence: 89%
“…Later studies by several groups showed that a single UNA modification at position 7 of the seed region (nucleotides 2–8 of the guide strand) strongly reduced miRNA-like off-target activity while maintaining the desired on-target activity of siRNAs. , The authors proposed that UNA modification reduced the off-target activity by thermodynamic destabilization of the seed–mRNA complex, which at position 7 was more critical for the partially complementary miRNA off-targets than for the fully complementary siRNA targets. , Consistent with this notion, other thermally destabilizing modifications, such as 2′-F/Me at position 7 (Figure ) or substitution of all eight seed ribonucleotides with DNA reduced the miRNA-like off-target activity of the modified guide strands. Beal and co-workers showed that the 1-ER triazole nucleobase substitution (Figure ) at the first position of the guide strand (G1) improved siRNA specificity by reducing the miRNA-like off-target activity while improving the on-target activity .…”
mentioning
confidence: 89%
“…As TNA has a short internucleotide length resulting in thermodynamically less stable duplexes, we reasoned that it should reduce off-target effects as was shown previously for the destabilizing GNA modification . To assess how TNA incorporation into the seed region impacts on- and off-target activity, we utilized a previously described dual-luciferase assay. , The parent GalNAc-siRNA ( si-72 , Table ) or versions containing TNA modifications at positions 5, 6, 7, or 8 in the antisense strand ( si-73 , si-74 , si-75 , and si - 76 , Table ) were co-transfected into COS-7 cells along with the reporter plasmid for the expression of control firefly luciferase and Renilla luciferase containing either a single on-target siRNA binding site in the 3′-untranslated region (3′-UTR) or four tandem sites that are complementary to the siRNA antisense seed region (positions 5–8) but not the rest of the antisense strand, in the 3′-UTR. The siRNAs with TNA modifications had on-target activity essentially equivalent to that of the parent siRNA as assessed using the reporter containing a single site fully matched to the antisense strand (Figure C,D).…”
Section: Resultsmentioning
confidence: 99%
“…Several RNAi-based therapeutics have been approved for clinical use including patisiran (ONPATTRO), givosiran (GIVLAARI), lumasiran (OXLUMO), inclisiran (LEQVIO), and vutrisiran (AMVUTTRA). In each case, appropriate chemical modification and efficient delivery were key to the successful approval. Natural RNA duplexes are metabolically unstable, and thus, for use as a therapeutic, the synthetic small interfering RNA (siRNA) must include chemically modified nucleotide-building blocks to prevent enzymatic degradation, to enhance lipophilicity, to improve cell-membrane permeability, and to mitigate immune responses and off-target effects . For example, patisiran contains 2′- O -methyl (2′- O Me) ribonucleotides and is formulated in lipid nanoparticles, and givosiran, lumasiran, inclisiran, and vutrisiran are chemically modified with 2′- O Me and 2′-deoxy-2′-fluoro (2′-F) ribonucleotides and conjugated to a trivalent N -acetylgalactosamine (GalNAc, Figure A,C,D). GalNAc is the ligand for the hepatic asialoglycoprotein receptor. This receptor mediates liver cell-specific uptake of the siRNAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) modifications. By chemically modifying siRNA nucleotides or by using analogs, numerous challenges associated with the development of siRNA therapeutics can be overcome (Akabane‐Nakata et al., 2021; Guenther et al., 2022; Jahns et al., 2022; Manoharan, 2004; Manoharan et al., 2011). Although unmodified or minimally modified siRNAs can induce gene silencing in vivo , particularly in tissues where the local application is feasible, substantial modifications can (i) effectively mitigate immunostimulatory siRNA‐induced activation of the innate immune response (Deleavey et al., 2010; Peacock et al., 2011), (ii) enhance chemical stability and efficacy (Bramsen et al., 2009; Choung et al., 2006; Corey, 2007), and (iii) reduce toxicity resulting from off‐target effects(Bramsen et al., 2010; Iribe et al., 2017; Neumeier & Meister, 2021; Snøve & Rossi, 2006).…”
Section: Introductionmentioning
confidence: 99%